A PALACE HAMMAM IN TURKEY: THE KUM KASRI HAMMAM - Ozakin, Rabia; Erdem, Ayten (DOLNOSLASKIE WYDAWNICTWO EDUKACYJNE-DWE, 2012)
The Kum Kasri Hammam is one of the buildings of the Yeni Saray complex in Edirne that have managed to survive to the present day. The Yeni Saray Complex is the oldest palace of the Ottoman Empire. The mid-15th century construction of the Hammam coincided with the building of Kum Pavilion (Kum Kasri). This hammam consists of a lukewarm area, two hot areas, the seclusion area, and the water storage area and it covered with domes and semi domes. The internal cuspidate and chamfered dome that covers the hot area of the bath is especially magnificent. The other features of the Hammam are the walls made up of alternating strips of brick and stone, a bare minimalist exterior, and an interior space with brick and plaster muqarnas inside the dome and semi-domes that function as transition points, along with hand drawn decorations. Over time, the hammam was deserted and the adjacent pavilion destroyed. The restoration of the building began in 2011. As part of the restoration. efforts, the later and unoriginal additions were removed, the closed-up entry door reopened, the remaining original materials, unique wall texture, and high quality period traces preserved, the surfaces cleaned, and the grouting and brick dust mortar renewed. The aim of this work is to compare the pre- and post-restoration features of this approximately 560 year old Hammam, to determine the extent to which the original and historical values of the building have been preserved, and thus to address the methods used in the restoration.
Keywords: Kum Kasri; Hammam; Palace; Restoration; Edirne-Turkey; Construction & Building Technology; Engineering